Immunotherapy in multiple myeloma. (2021) - Jadoon, Yamna; Siddiqui, Mustaqeem A.
Highlights: Immunotherapy for multiple myeloma is a new and expanding field. Several novel targets have been identified. Bispecific, trispecific, and antibody drug conjugates are new constructs that have shown clinical efficacy. Preliminary results of multiple immunotherapies show promise in inducing long term remissions in heavily pre-treated patients. Abstract: Despite available therapies, Multiple Myeloma (MM) remains an incurable hematologic malignancy. Over the past three decades, there have been tremendous developments in therapeutic options for MM. In regards to immunotherapy, Daratumumab was the first monoclonal antibody to receive FDA approval for multiple myeloma. Since then, other monoclonal antibodies such as elotuzumab and isatuximab have received FDA approval. Many clinical trials are underway investigating the efficacy of newer immunotherapies. This review summarizes recently presented and/or published data regarding this growing field, specifically regarding monoclonal antibodies, antibody-drug conjugates, bispecific antibodies, and trispecific antibodies.